2022
DOI: 10.3847/2041-8213/ac897a
|View full text |Cite
|
Sign up to set email alerts
|

Migratory Outbursting Quasi-Hilda Object 282P/(323137) 2003 BM80* **

Abstract: We report that object 282P/(323137) 2003 BM80 is undergoing a sustained activity outburst, lasting over 15 months thus far. These findings stem in part from our NASA Partner Citizen Science project Active Asteroids (http://activeasteroids.net), which we introduce here. We acquired new observations of 282P via our observing campaign (Vatican Advanced Technology Telescope (VATT), Lowell Discovery Telescope (LDT), and the Gemini South telescope), confirming 282P was active on UT 2022 June 7, some 15 months after … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…In addition to its residence on the tenuous T J = 3 asteroidcomet boundary, 2009 DQ 118 exhibits many dynamical similarities to other active quasi-Hildas, such as 282P (Chandler et al 2022). At a ≈ 3.6 au, 2009 DQ 118 sits slightly outside of the quasi-Hilda semimajor axis range of ∼3.7 au < a < ∼4.2 au given by Toth (2006), placing it closer to the Cybele asteroid group than to the Hildas.…”
Section: Dynamical Classificationmentioning
confidence: 91%
See 2 more Smart Citations
“…In addition to its residence on the tenuous T J = 3 asteroidcomet boundary, 2009 DQ 118 exhibits many dynamical similarities to other active quasi-Hildas, such as 282P (Chandler et al 2022). At a ≈ 3.6 au, 2009 DQ 118 sits slightly outside of the quasi-Hilda semimajor axis range of ∼3.7 au < a < ∼4.2 au given by Toth (2006), placing it closer to the Cybele asteroid group than to the Hildas.…”
Section: Dynamical Classificationmentioning
confidence: 91%
“…Thermal fracture is primarily applicable for near-Earth asteroids that experience large temperature gradients (several hundred degrees) over their orbits (see Chandler et al 2022;Jewitt & Hsieh 2022 and references therein). Additionally, observations of objects that are likely candidates for thermal fracture-driven activity have found either a lack of evidence for activity for 2005 UD (Kueny et al 2023), or, for (3200) Phaethon, that the observed activity is likely associated with gas emission rather than thermal fracture (Hui 2023); hence, this is an unlikely mechanism to explain the activity seen on 2009 DQ 118 .…”
Section: Activity Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…This dynamical class shares a name with the Hilda asteroids, a small body population bound in stable 3:2 interior mean motion resonance (MMR) with Jupiter, and span a region from the outer asteroid belt to the Jupiter Trojans (Szabó et al 2020). However, quasi-Hildas are not in true resonance with Jupiter, though their orbits are reminiscent of the Hildas when observed in the Jupiter corotating reference frame (Chandler et al 2022), as discussed later in Section 6. Consequently, these objects are challenging to identify, with dynamical modeling requisite to confirm a quasi-Hilda orbit confidently.…”
Section: Introductionmentioning
confidence: 89%
“…We initially created the Hunting for Activity in Repositories with Vetting-Enhanced Search Techniques (HARVEST) pipeline for our proof-ofconcept work, Searching Asteroids For Activity Revealing Indicators (SAFARI; Chandler et al 2018). Since then, we have substantially improved upon and optimized HARVEST (Chandler et al 2019(Chandler et al , 2020(Chandler et al , 2021(Chandler et al , 2022Chandler 2022), so we provide here a comprehensive description of the complete system.…”
Section: Harvest: the Image Cutout Pipelinementioning
confidence: 99%